1945
DOI: 10.1128/jb.49.4.317-334.1945
|View full text |Cite
|
Sign up to set email alerts
|

The So-Called GenusCandidaBerkhout, 1923

Abstract: mark the principal stages in the development of knowledge regarding the nonascosporogenous and filamentous yeasts called "monilias." During the past years several new papers have been published. They may be classified in two groups in accordance with the procedures used for the identification of the species within the genus Candida. Martin et al. (1937) and Martin and Jones (1940) adopted the method summarized by Conant (1940), whose procedures are as follows: (a) appearance of the growth in Sabouraud's glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1946
1946
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Further confusion was added by the results of Mackinnon and Artagaveytia-Allende (1945). Using Lodder's auxanographic technique, these authors found C. pelliculosa able to utilize asparagine and peptone but not ammonium sulfate or urea.…”
mentioning
confidence: 99%
“…Further confusion was added by the results of Mackinnon and Artagaveytia-Allende (1945). Using Lodder's auxanographic technique, these authors found C. pelliculosa able to utilize asparagine and peptone but not ammonium sulfate or urea.…”
mentioning
confidence: 99%
“…C. albicans genomic libraries were either obtained in-house (in plasmid YEp13 from strain SC5314; Gillum et al, 1984) or were kindly provided by Dr S. Scherer (in plasmid pSS1041 from strain 655 (ATCC56884); Goshorn et al, 1992) or Dr Y. Koltin (in plasmid pYSK35 from strain B-792; Fling et al, 1991). C. albicans strains used in chromosome blots were clinical isolates: strain 2023 (ATCC10261; MacKinnon et al, 1945), A-81Pu (Kwon-Chung and Hill, 1970), B-311, B-792, FC18 (ATCC62376; Whelan and Magee, 1981) and SC5314 (Bristol-Myers Squibb Culture Collection).…”
Section: Yeast Strains and Librariesmentioning
confidence: 99%
“…The mycelium is entirely a pseudomycelium, never a true mycelium as sometimes is found in C. albicans, for instance. Mackinnon and Artagaveytia-Allende (169,171) have called attention to the fact that this species is very like, probably identical with, Mycoderma cerevisiae and indeed Mackinnon (168) that the perfect stage of many species of Candida is Saccharomyces (68), but it is evident that the perfect stage of C. Krusei and of Mycoderma would be Pichia. The possibility of C. Krusei being the dissociated stage of Mycoderma should be investigated.…”
Section: ] 241mentioning
confidence: 99%